Diseño de un cuadro de mando integral en una empresa de servicios públicos (2018)
This monograph presents the design of an Integral Control Panel of a public company that provides water and sewerage services. For the elaboration of this table, different factors of the operation and purpose of the company are analyzed in order to generate a strategy aligned with this to finally determine with the CMI the key points that must be monitored so that the company has a direction aligned to the strategy, which will allow measuring the results and generating permanent improvement actions, taking as a focus the generation of value of the intangible assets of the company.